Penguatan Identitas Usaha Melalui Pendampingan Digital Marketing Dan Branding UMKM Bandeng Presto Restu Ibu Di Kabupaten Rembang - Zauza’ Fithriyah; Desita Aliyya Zahra; Rahma Ayu Anggita; Adelia Ika Damayanti (Pusmedia Group Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting economic growth and community welfare. However, many MSME actors still experience challenges in adopting digital technology and strengthening business identity. These challenges were also experienced by Bandeng Presto Restu Ibu MSME in Rembang Regency, which has potential superior products but has not optimized branding, digital marketing, business location accessibility, and administrative management. This community service activity aims to strengthen business identity through digital marketing and branding assistance to improve MSME visibility and competitiveness. The implementation method used a Participatory Action Research (PAR) approach through several stages, including problem identification, program planning, implementation of assistance activities, and evaluation. Data collection techniques included observation, interviews, documentation, and participatory evaluation with business owners. The assistance programs included developing business identity through logos, banners, and product stickers, creating Google Maps location profiles, developing social media platforms, and preparing simple bookkeeping systems. The results showed that the assistance program improved the MSME’s ability to utilize digital media as a promotional tool, strengthened product identity, and facilitated consumers in accessing business information. This activity is expected to become a strategic effort for Bandeng Presto Restu Ibu MSME to expand market reach and achieve sustainable business development.